(3efgGL GdgOGjI Edi CMcGe GdTQjYI haQhY Gdabgs - (3GdcQHGSj, , GdcQHGSj, eMeO Hf EHQGgje Hf eMeO MSf, J (B1260(3g` (B1844(3es ((3YHO GdcQje Hf eMeO QMje GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj gOGfG Edi eYGde GdESdGe (B... (3cJGH aj GdYHGOGJ, GdWgGQI hajg efGgL, GdefgL GdChd aj GdhVhA heG jJYdb Hg, gOGjI EfeG jLH GdhVhA ddhGLH ef GdUdGIs
(3BNQgG (B:s
(3BNQgG(B: (3aaj GdNH(B: (3eG JedC QLdG HYO Cf jUdj GdYTGA GdBNQI aHGJ Jdc GddjdI EdG hfaSg JfGRYg Edi GdMQGe, hef Ccdg HGddjd VQH Ydjg YQb GdLPGe (B.. (3hHGJ jfRa GdOe, haj GdNHQ eG CMb HYV GdfGS jbhdhf Cfg jfHJ aj hGO Lgfe (B... (3hCUhdg jbWY GdHdZes
(3JHUQI GdeDda (B:s
(3CQN UGMH GdPQjYI haGJg, SfI (B1262(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGf, L (B5: 305s
(3GdPQjYI, L (B23: 113s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis